Peran Ekonomi Kreatif Terhadap Kesejahteraan Masyarakat (Studi Kasus Pada Kabupaten di Provinsi Lampung) - Madnasir Madnasir; Mohammad Fikri Nugraha Kholid (JURNAL ILMIAH EDUNOMIKA, 2024)
The creative economy is predicted to be the future industry as the fourth wave industry, which focuses on creative concepts and ideas. The existence of the creative economy is proof that business opportunities are increasing, because the more modern technology is currently adding activities that are useful for the millennial community. With the development of the creative economy, it will have an impact on the welfare of a society. This study will discuss how the role of the creative economy on people's welfare and creative economy strategies in improving the welfare of the people of urban districts in the province of Lampung. This research will use the type of field research (field research) that is looking for data directly in the field or research location and is descriptive qualitative, with the aim of describing events in the field such as certain behaviors and activities in detail. The sample in this study is the community of creative economy actors in MSMEs in the City and Regency of Lampung Province. This study uses five samples of the creative economy in districts in Lampung province, namely the Processed Producer Group of Soybean Tofu and Tempe in Sawah Brebes, Bandar Lampung City, Group of Tapis Embroidery Craftsmen in Tanggamus, Processed Kencur in Fajar Bulan Village in Central Lampung, Bamboo Weaving Craftsmen. Tegal Sari Village, Gading Rejo, and Organic Vegetable Farmer Group in Metro City. Based on the results of the study, it was found that the existence of creative economic activities has played a role in realizing prosperity for them. And based on the results of the analysis of the creative economy strategy in five samples, it is stated that the strategy that the creative economy strategy of the regency city in Lampung province that can be applied is in the SO strategy, because this creative economy strategy can support the realization of increasing public welfare in the future.